PERANAN IKLIM SEKOLAH TERHADAP PEMBENTUKAN KARAKTER SISWA SMP METTA MAITREYA PEKANBARU (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract Education is a part of conscious and organized effort to form learning atmosphere amd learning process in order to make students develop their potential actively and have spiritual spirit, self control, personality, intelligent, noble attitude, and skills that are needed for themselves, society, and nation. The positive situation at school has a role to successful achievement of national education with the awareness of the importance of education to develop human resource and nation character. Metta maitreya school is the only school which has motto âA World As One Familyâ by practicing love value moral and ethic in daily life to make the students act wisely. This research was conducted to know and analize the school climate to the studentsâ character.This research used qualitative approach. The sample of this research was students of SMP Metta Maitreya Pekanbaru. The sampling technique used was strata sampling, in which there was sample in each strata. The subject was 60 students. Data collection techniques were quetionnaire, interview, and observation. From the data analysis, it was found that school climate influences the form of SMP Metta Maitreya studentâs character.The result of the research showed that the positive school environment was useful in solving problems at school. The positive climates at school such as the teachersâ willingness to greet students, the awareness of students to ask permission if they want to drink in the class, and respect between teachers and students at school can decrease behavior problems at school, increase students motivation to study, give more attention to the students, and improve students academic achievement.Keywords: School Climate, Studentsâ Character